GIM EDUKASI “IMUNEED QUEST” MATERI SISTEM IMUN UNTUK SISWA FASE F KURIKULUM MERDEKA - Susila, Gusti Kade Dwi Dharma; Ni Putu Sri Ratna Dewi; Ajeng Purnama Heny (Undiksha, 2024)
The research aims to produce a valid and practical digital educational games as a learning media for the immune system material for students in Phase F of the Curriculum Merdeka. This research is a type of research and development (R&D) was used the Borg & Gall development model up to the fifth stage. The study was conducted with biology teachers and eleventh-grade students at SMA Negeri 1 Kuta Utara. The validity test was conducted by material experts and media experts. The practicality test was carried out on three biology teachers and 30 eleventh-grade students at SMA Negeri 1 Kuta Utara. Data analysis was performed using qualitative descriptive analysis. Research results show that: (1) The Imuneed Quest educational game build plan developed consists of a home page, a login page, the main page, an information page, mission pages, how to play page, and playing page that contains immune system materials. (2) Media validation received a rate of 4.5 which includes criteria very valid. Validation of material obtained from a range of all aspects of 4.3 is highly valid. (3) Imuneed Quest educational game practicality test results from the teacher's response received a percentage of 85% from the category very practical and the student's reply received a percentage of 87% from the category very practice.